Synthesis and biological assessment of KojoTacrines as new agents for Alzheimer's disease therapy. (1st January 2019) - Dgachi, Youssef; Martin, Hélène; Malek, Rim; Jun, Daniel; Janockova, Jana; Sepsova, Vendula; Soukup, Ondrej; Iriepa, Isabel; Moraleda, Ignacio; Maalej, Emna; Carreiras, M. Carmo; Refouvelet, Bernard; et al.
Abstract: In view of the multifactorial nature of Alzheimer's disease (AD), multitarget small molecules (MTSM) represent the most potent and attractive therapeutic strategy to design new drugs for Alzheimer's disease therapy. The new MTSM KojoTacrines (KTs) were designed and synthesized by juxtaposition of selected pharmacophoric motifs from kojic acid and tacrine. Among them, 11-amino-2-(hydroxymethyl)-12-(3-methoxyphenyl)-7, 9, 10, 12-tetrahydropyrano [2', 3':5, 6] pyrano[2, 3- b ]quinolin-4(8 H )-one (KT2d ) was identified as less-hepatotoxic than tacrine, at higher concentration, a moderate, but selective human acetylcholinesterase inhibitor (IC50 = 4.52 ± 0.24 µM), as well as an antioxidant agent (TE = 4.79) showing significant neuroprotection against A β 1–40 at 3 µM and 10 µM concentrations. Consequently, KT2d is a potential new hit-ligand for AD therapy for further biological exploration. Graphical Abstract: